The influence of visual marketing on consumers' purchase intention of fast fashion brands in China–An exploration based on fsQCA method - Zhang, Yaqiong; Huang, Shiyu (Frontiers in Psychology, 2024)
Under the rapid development of e-commerce, offline brick-and-mortar stores have been severely impacted. However, the importance of the visual, sensory and even psychological experience in the apparel industry makes offline stores still irreplaceable. The impact on consumers' visual experience cannot be ignored and is a significant influencing factor in determining consumers' psychological change and purchase intention. Especially for fast fashion brands which pursue low costs, visual marketing strategies is a cost-effective marketing tool to enhance the visual experience. In this paper, by adapting SOR theory and using fuzzy set qualitative comparative analysis (fsQCA) research method, 15 fast fashion apparel brands and 374 valid questionnaires are adapted in China to explore not only the influence of individual dimensions in visual marketing on consumers' purchase intention, but also the action of multi-dimensional combinations, and the research finds that: (1) there are two driving paths for high consumers' purchase intention. The first path is a combination of high clarity of arrangement and low display density; the second path is a combination of low light intensity, high clarity of arrangement, high tonal harmony and high window appeal. (2) There are also two paths that drive non-high consumers' purchase intentions, and they are asymmetrically related to the paths that drive high consumers' purchase intentions. The findings of this study help to provide direction and suggestions for offline visual marketing strategies of fast fashion apparel brands to increase consumers' psychological perception and purchase intention through a range of visual presentation techniques.